COVID-induced 3 weeks’ treatment delay may exacerbate breast cancer patient’s psychological symptoms - Wang, Yijia; Yang, Yuqing; Yan, Changjiao; Ma, Wen; Yang, Jixin; Wei, Hongliang; Li, Nanlin (Frontiers in Psychology, 2022)
The delayed access to cancer treatment due to the outbreak of COVID-19 pandemic posed a unique challenge to breast cancer patients and caused a significant level of mental distress among them. In the current research, we examined the psychological impacts of COVID on a subpopulation of breast cancer patients from a hospital in Shaanxi province of China using Symptom Checklist-90-R (SCL-90-R). Participants were 195 breast cancer patients at the outpatient clinic of Xijing hospital, Xi’an, Shaanxi Province, China. We found that a treatment delay of more than 3 weeks may exacerbate breast cancer patients’ psychological symptoms, such as somatization, obsessive-compulsive disorder, interpersonal sensitivity, depression, hostility, phobic anxiety, paranoid ideation, and psychoticism, whereas a short-term delay of less than 3 weeks is less likely to have a significant effect on one’s mental well-being. Additionally, breast cancer survivors, especially those at more advance stages, tend to experience more elevated psychological symptoms with longer treatment delay, and whose treatments continues to be delayed reported stronger psychological symptoms than individuals whose treatment are resumed, regardless of treatment type.